2018
DOI: 10.1111/ijpo.12267
|View full text |Cite
|
Sign up to set email alerts
|

Low maternal vitamin D status in pregnancy increases the risk of childhood obesity

Abstract: Exposure to very low 25(OH)D concentrations in utero may increase childhood adiposity indices. Given that vitamin D is a modifiable risk factor, our findings may have important public health implications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
38
2
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(46 citation statements)
references
References 29 publications
(42 reference statements)
3
38
2
3
Order By: Relevance
“…A growing body of evidence suggests that maternal vitamin D status in pregnancy may play a part in the offspring adipogenesis [185][186][187][188][189]; however, not all studies are in agreement [190,191]. Tint et al conducted a study to examine the association between maternal 25(OH)D status at mid-gestation and neonatal abdominal adipose tissue (AT) compartments.…”
Section: Offspring Soft Tissue Body Compositionmentioning
confidence: 99%
“…A growing body of evidence suggests that maternal vitamin D status in pregnancy may play a part in the offspring adipogenesis [185][186][187][188][189]; however, not all studies are in agreement [190,191]. Tint et al conducted a study to examine the association between maternal 25(OH)D status at mid-gestation and neonatal abdominal adipose tissue (AT) compartments.…”
Section: Offspring Soft Tissue Body Compositionmentioning
confidence: 99%
“…For example, rodent studies have demonstrated that maternal vitamin D deficiency leads to adult onset cardiovascular dysfunction that is associated with elevated blood pressure, perturbed heart rate and cardiac hypertrophy . Vitamin D deficiency during pregnancy is also associated with increased adiposity in childhood . Maternal vitamin B deficiencies have been linked to epigenetic alterations and DNA methylation, associated with overweight offspring, an impaired immune response, hypertension and metabolic insulin resistance …”
Section: Long Term Effects Of Micronutrient Deficiencies On Offspringmentioning
confidence: 99%
“…26 Vitamin D deficiency during pregnancy is also associated with increased adiposity in childhood. 27 Maternal vitamin B deficiencies have been linked to epigenetic alterations and DNA methylation, associated with overweight offspring, an impaired immune response, hypertension and metabolic insulin resistance. 28 Through models such as these, it has become evident that key organ systems are central to long term disease.…”
Section: Magnesium Deficiency Hasmentioning
confidence: 99%
“…The measurements were conducted at Karolinska Institutet, Sweden, using inductively coupled plasma mass spectrometry (ICPMS; Agilent 7700x, Agilent Technologies, Tokyo, Japan) (21). The urine samples were diluted 1:10 in 1% nitric acid (prepared from 65% suprapur, Merck, Darmstadt, Germany (23,24). These internally generated SD scores were preferred for this study over external growth reference curves (e.g.…”
Section: Sample Collection and Trace Element Analysesmentioning
confidence: 99%